Stigma and Alzheimer’s Disease and Related Dementias: A Systematic Review of Relatives’ Experiences - Provias, Georgios; Karampasis , Christos; Theofanidis, Dimitrios (Health & Research Journal, 2026)
Objective: This systematic review examines the multifaceted stigma experienced by relatives of individuals living with Alzheimer’s Disease and related dementias (ADRD). Methods: A comprehensive search of the PubMed and Scopus databases was conducted, resulting in the identification of eighteen relevant studies published within the last five years. These studies were then subjected to rigorous analysis. Results: The findings reveal that family, cultural, social, and psychiatric stigma have a significant impact on caregivers, leading to increased burden, social isolation, delayed help-seeking, and psychological distress. The analysis further underscores the pivotal role of cultural beliefs and societal norms in shaping the manifestation and intensity of stigma across diverse contexts, including collectivist societies and immigrant communities. The review also explores the complex relationship between diagnostic disclosure, particularly with the advent of biomarkers, and the potential for increased stigma. Additionally, the review designates the need for further research on the experiences of LGBT+ caregivers, who often face a heightened level of stigma. Conclustions: This study concludes with an emphasis on the necessity of interventions, including public education and culturally sensitive support systems, to mitigate the detrimental effects of stigma on ADRD caregivers.